The concordance rate of non‐chromosomal congenital malformations in twins based on zygosity: a retrospective cohort study. (10th September 2020) - Jung, YM; Lee, SM; Oh, S; Lyoo, SH; Park, C‐W; Lee, SD; Park, JS; Jun, JK
Abstract : Objective: To examine the concordance rate of non‐chromosomal congenital malformations in twin pairs based on zygosity. Design: Retrospective cohort study. Setting: A tertiary hospital in Korea. Population: Twin pairs born at Seoul National University Hospital between 2001 and 2019. Methods: Congenital malformations were diagnosed by postnatal workups of neonates or autopsy in cases of stillborn infants. Zygosity was confirmed by sex, chorionicity and DNA analysis. Main outcome measures: Concordance rate of congenital malformations in twin pairs based on zygosity. Results: In total, 3386 twin pairs were included. The risk of a congenital malformation in the index twin increased significantly if the co‐twin had the congenital malformation, and the concordance rate was higher in monozygotic (MZ) than in dizygotic (DZ) twins (37.04 versus 16.77, P  < 0.001). An increased risk of a congenital malformation in the presence of the same congenital malformation in the co‐twin was observed only for malformations of the nervous system, eye/ear/face/neck, circulatory system, cleft lip/palate, genital organs, urinary system and musculoskeletal system. Significantly higher concordance rates in MZ than in DZ twin pairs were observed only for the nervous system (40.00 versus 0.00, P  < 0.001), circulatory system (32.97 versus 19.74, P  = 0.021), cleft lip/palate (44.44 versus 0.00, P  = 0.017) and urinary system (22.22 versus 0.00, P  = 0.004), whereas significant differences were not found for the genital organs or musculoskeletal system. Conclusions: Monozygotic twins had higher concordance rates than DZ twins only in specific organ systems. It may be speculated that nervous system, circulatory system, cleft lip/palate and urinary system are primarily genetically affected. Tweetable abstract: Monozygotic twins had higher concordance rates than dizygotic twins only in specific organ systems. Tweetable abstract: Monozygotic twins had higher concordance rates than dizygotic twins only in specific organ systems.